Dramatherapy and autism - Haythorne, Deborah; Seymour, Anna (London Routledge, 2017)
"Using extensive examples from practice with a range of client groups, Dramatherapy and Autism confronts the assumption that people with autism are not able to function within the metaphorical realms of the imagination and creativity. It demonstrates that not only are people who function along the spectrum capable of engaging in creative exploration, but that through encountering these processes in the clinical context of dramatherapy, changes can be made that are life enhancing. Bringing in cutting-edge research and practice on dramatherapy, Dramatherapy and Autism aims to contribute to developing the theory and practice of creative arts therapies interventions with clients with autism. The book is part of the Dramatherapy: approaches, relationships, critical ideas series, in which leading practitioners and researchers in the field develop the knowledge base of this unique discipline, whilst contextualising and acknowledging its relationship with other arts and therapeutic practices."--Provided by publisher.
Keywords: Autism -- Treatment; Drama -- Therapeutic use